2015
DOI: 10.1038/srep08802
|View full text |Cite
|
Sign up to set email alerts
|

An efficient strategy for producing a stable, replaceable, highly efficient transgene expression system in silkworm, Bombyx mori

Abstract: We developed an efficient strategy that combines a method for the post-integration elimination of all transposon sequences, a site-specific recombination system, and an optimized fibroin H-chain expression system to produce a stable, replaceable, highly efficient transgene expression system in the silkworm (Bombyx mori) that overcomes the disadvantages of random insertion and post-integration instability of transposons. Here, we generated four different transgenic silkworm strains, and of one the transgenic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…These results are consistent with previous studies that reported the background expression of a Bombyx nuclear receptor Ftz-F1 gene (BmFtz-F1) or the piggyBac transposon gene (PBase) under the control of the hsp70 promoter in transgenic silkworms (Uhlirova et al 2002). Although the basal activity of the hsp70 promoter was low at 25°C, our present study again confirms that the hsp70 promoter is a very effective inducible promoter for regulating the expression of exogenous genes in transgenic silkworms (Long et al 2015a). It is noteworthy that the persistent expression of the FLP recombinase did not have any adverse effects on development, health, and reproduction during the rearing of all of the H-H and H-A silkworms and different types of hybrid offspring (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are consistent with previous studies that reported the background expression of a Bombyx nuclear receptor Ftz-F1 gene (BmFtz-F1) or the piggyBac transposon gene (PBase) under the control of the hsp70 promoter in transgenic silkworms (Uhlirova et al 2002). Although the basal activity of the hsp70 promoter was low at 25°C, our present study again confirms that the hsp70 promoter is a very effective inducible promoter for regulating the expression of exogenous genes in transgenic silkworms (Long et al 2015a). It is noteworthy that the persistent expression of the FLP recombinase did not have any adverse effects on development, health, and reproduction during the rearing of all of the H-H and H-A silkworms and different types of hybrid offspring (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Our previous study suggested that continuous and repeated HST at 42°C in the embryonic stage of transgenic silkworms is the most effective way to regulate the in vivo expression of exogenous genes that were under the control of the hsp70 promoter (Long et al 2015a); thus, the same HST strategy was used in this study. The results suggested that compared with the offspring of TTS&H-H-1 individuals in the non-HST control groups, the excision efficiencies of the FRT-flanked target DNA were significantly higher in the offspring of TTS&H-H-1 individuals in the HST groups, although the frequencies of positive broods among site-specific excision in transgenic silkworms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the baculovirus-infected silkworm is a binary and transient recombinant protein production system. Thus, various investigators began to genetically transform silkworms with DNA constructs encoding the protein of interest under the transcriptional control of either whole body (Tamura et al, 2000) or silk gland-specific promoters (Adachi et al, 2006; Hino et al, 2006; Iizuka et al, 2009; Iizuka et al, 2013; Kojima et al, 2007; Kurihara et al, 2007; Kuwana et al, 2014; Long et al, 2015; Ogawa et al, 2007; Royer et al, 2005; Seong et al, 2011; Teule et al, 2012; Tomita et al, 2007; Tomita et al, 2003; Wang et al, 2014; Wen et al, 2010; Xu, 2014; Yanagisawa et al, 2007; reviewed in Tomita, 2011). This new, single component approach provided a stable, rather than transient source of recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The silkworm, Bombyx mori, is an economically important insect that has been completely domesticated by humans, and is also a classic model organism belonging to the second largest insect order, Lepidoptera. With the mapping of the silkworm genome (Mita et al, 2004;Xia et al, 2004), fine mapping (Xia et al, 2009), and the establishment and improvement of transgenic (Tamura et al, 2000;Long et al, 2014) and gene editing technology (Wang et al, 2013a;Liu et al, 2014;Ma et al, 2012Ma et al, , 2014, the discovery, research and use of genes have become a major research fields in the post genome era. Tissue-specific genes and their promoters are widely applied in developmental biology and molecular biology in processes, such as stem cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%